2015
DOI: 10.1002/pip.2718
|View full text |Cite
|
Sign up to set email alerts
|

On the interplay of cell thickness and optimum period of silicon thin‐film solar cells: light trapping and plasmonic losses

Abstract: Light trapping and photon management in honeycomb-textured microcrystalline silicon solar cells are investigated experimentally and by modeling of the manufacturing process and the optical wave propagation. The solar cells on honeycombtextured substrates exhibit short circuit current densities exceeding 30 mA/cm 2 and energy conversion efficiencies of up to 11.0%. By controlling the fabrication process, the period and height of the honeycomb-textured substrates are varied. The influence of the honeycomb substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 39 publications
(95 reference statements)
4
50
0
Order By: Relevance
“…The area filling factor of the nanowire is equal to (D/P) 2 . A constant unit cell period of 900 nm is chosen for these simulations as previous studies have shown that the optimal period of the surface texture is approximately equal to the thickness of the solar cell [9]. The diameter of the nanowire is varied from 50 nm to 900 nm corresponding to area fill factors ranging from 0.3% to 100%.…”
Section: Solar Cells With Textured Silicon Absorbersmentioning
confidence: 99%
See 3 more Smart Citations
“…The area filling factor of the nanowire is equal to (D/P) 2 . A constant unit cell period of 900 nm is chosen for these simulations as previous studies have shown that the optimal period of the surface texture is approximately equal to the thickness of the solar cell [9]. The diameter of the nanowire is varied from 50 nm to 900 nm corresponding to area fill factors ranging from 0.3% to 100%.…”
Section: Solar Cells With Textured Silicon Absorbersmentioning
confidence: 99%
“…The 3D diffraction grating (nanowire array) leads to a higher quantum efficiency and short circuit current density compared to 2D diffraction gratings (line grating). approximately equal to the thickness of the solar cell [9]. The diameter of the nanowire is varied from 50 nm to 900 nm corresponding to area fill factors ranging from 0.3% to 100%.…”
Section: Solar Cells With Textured Silicon Absorbersmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence the short-circuit current density is reduced to 19.3 mA cm −2 . [65] In the current study, we have used a flat aluminum reflector, while the NiO/ITO layer is textured. [63,64] By inserting an interlayer with a low refractive index, the plasmon resonance wavelength can be shifted to short wavelengths.…”
Section: Light Incoupling In Solar Cells With Low Refractive Index/pementioning
confidence: 99%